The Web and Linked Data as a Solid Foundation for Dataspaces - Meckler, Sascha; Dorsch, Rene; Henselmann, Daniel; Harth, Andreas (ACM Web Conference 2023 - Companion of the World Wide Web Conference, WWW 2023, 2023)
The concepts for dataspaces range from database management systems to cross-company platforms for data and applications. In this short paper, we present the "Solid Data Space"(SDS), a concept for dataspaces that build on top of the (Semantic) Web and Social Linked Data (Solid). Existing Web technologies and Linked Data principles form the foundation for open, decentralized networks for sovereign data exchange between citizens, organizations and companies. Domain-specific dataspace implementations can extend the agreements for communication and collaboration to enable specific functionality. We compare the SDS with principles and components of the emerging International Data Spaces to identify similarities and point out technological differences.
Created from Fastlane, Scopus look-up
Keywords: Dataspace; International Data Spaces; Social Linked Data (Solid)